2017
DOI: 10.2174/1574886311666160803111401
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Opioid Abuse and its Potential Role in Gross Dental Decay

Abstract: Prescription opioids are addictive, have high abuse potential, and dentists contribute to this problem by overprescribing these drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…For example, a recent USA study found that dentists accounted for 10% of all antibiotic prescription, but 81% of the antibiotics prescribed by dentists were deemed unnecessary 7 . The overuse of medications such as benzodiazepines and opioids can also lead to serious side-effects and risks, including overdose and addiction 8 . According to a recent cross-sectional analysis, 55% of the dentists in Australia reported overprescribing of antibiotics, 46% prescribing inappropriate anxiolytics, and 16%–27% prescribing analgesics over anti-inflammatories 9 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent USA study found that dentists accounted for 10% of all antibiotic prescription, but 81% of the antibiotics prescribed by dentists were deemed unnecessary 7 . The overuse of medications such as benzodiazepines and opioids can also lead to serious side-effects and risks, including overdose and addiction 8 . According to a recent cross-sectional analysis, 55% of the dentists in Australia reported overprescribing of antibiotics, 46% prescribing inappropriate anxiolytics, and 16%–27% prescribing analgesics over anti-inflammatories 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, twenty-five thousand patients in the European Union and more than 63,000 patients in the U.S. have lost their lives [ 2 ] due to hospital-acquired bacterial infections [ 8 ]. A study [ 9 ] investigating the correlation between xerostomia and medications in a long-term cross-sectional study, demonstrated that opioid (Vicodin® and Percocet®) abusers typically display diminished salivary flow, poor oral hygiene and increased sugar consumption [ 10 ] The combination of the factors cited results in the development of gross dental decay and other systemic conditions (e.g., insulin resistance and diabetes) [ 11 ] Therefore, the development of devices and techniques capable of effectively treating inflammation without the utilization of drugs is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…У фаховій науковій літературі наводяться дані про вплив опіоїдів на ряд органів як у клінічних випадках, так і в умовах експерименту [3,4]. Тривале зловживання опіоїдів провокує розвиток виражених патологічних змін зубощелепної системи, що утруднює проведення диференціальної діагностики та лікування патології органів ротової порожнини, пародонта [5,6]. З метою ефективності комплексного лікування захворювань пародонта у наркозалежних осіб важливим є застосування патогенетичних препаратів, яким властива протизапальна та антибактеріальна дії [7,8].…”
Section: Conclusion the Use Of The Combined Action Of Drugs Pentoxifylline And Ceftriaxone Causes A Protective Effect Favorably Affectingunclassified